2011
DOI: 10.1007/s10620-011-1981-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Suitable Reference Genes for qPCR Analysis of Serum microRNA in Gastric Cancer Patients

Abstract: Our results demonstrated that reference gene choice for qPCR data analysis has a great effect on the study outcome, and that it is necessary to choose a suitable reference for reliable expression data. We recommend miR-16 and miR-93 as suitable reference genes for serum miRNA analysis for gastric cancer patients and healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
213
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(223 citation statements)
references
References 34 publications
6
213
2
2
Order By: Relevance
“…Based on the different normalization strategies, miR-101a was determined to be the most optimal and stable reference gene. Furthermore, mir-101a was also demonstrated to be ideal for normalization of serum microRNA in gastric cancer patients (38).…”
Section: A B Cmentioning
confidence: 99%
“…Based on the different normalization strategies, miR-101a was determined to be the most optimal and stable reference gene. Furthermore, mir-101a was also demonstrated to be ideal for normalization of serum microRNA in gastric cancer patients (38).…”
Section: A B Cmentioning
confidence: 99%
“…In their study targeting serum miRNA in gastric cancer patients, Song et al demonstrated that RNU6B could not be detected in almost half of the serum samples; in the other half of patients, it was detected with Ct values of >40. Moreover, RNU6B was less stably expressed than let-7a and miR-16 in normal and cancerous human solid tissues (25). Although we actually examined the same study using RNU6B for normalization, there was marked variation in Ct values when comparing CCC patients and HCs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…miR-103 (5p, TaqManID: 121218) and miR-191 (5p, TaqManID: 002299) [10]. All selected miRNAs are identified as potential biomarkers for various diseases, confirming there relative abundancy in serum [9,[11][12][13][14].…”
Section: Patients and Mirna Selectionmentioning
confidence: 92%